2021
DOI: 10.1038/s41598-021-83444-1
|View full text |Cite
|
Sign up to set email alerts
|

BOOSTing patient mobility and function on a general medical unit by enhancing interprofessional care

Abstract: Low mobility during hospitalization remains prevalent despite associated negative consequences. The goal of this quality improvement (QI) project was to increase patient mobility and function by adding a physical therapist (PT) to an existing interprofessional care team. A mobility technician assisted treatment group patients with mobility during hospitalization based on physical therapist recommendations. Change in functional status and highest level of mobility achieved by treatment group patients was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This is attributed to the prioritization of COVID-positive and PUI patients and seeing patients with negative COVID results, if able. Wood et al 5 reported an increased length of stay due to an increased case-mix index, and Johnson et al 1 contribute an increased length of stay to failure to control for confounding variables.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is attributed to the prioritization of COVID-positive and PUI patients and seeing patients with negative COVID results, if able. Wood et al 5 reported an increased length of stay due to an increased case-mix index, and Johnson et al 1 contribute an increased length of stay to failure to control for confounding variables.…”
Section: Discussionmentioning
confidence: 99%
“…Immobility affects every body system and leads to costly hospital-acquired complications, including delirium, pneumonia, venous thromboembolism, pressure injury, and falls. [1][2][3][4][5] In addition to the hospitalacquired complications, immobility leads to functional decline, especially in the older adult. [1][2][3][4][5][6][7][8] During a single hospital admission, bed rest can lead to functional decline as quickly as 72 hours from admission because of muscle atrophy in a healthy adult.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…16 A functional assessment is considered the key assignment for PTs and occupational therapists (OTs), and early involvement of the PT has been shown to facilitate an earlier delivery of walking devices. 17 Unfortunately, the functional assessment is typically followed by a recommendation of mobilization targeting the entire nursing staff 6,[18][19][20] This is, however, an inconvenient situation, as it is known that recommendations with no clear assignation of responsibility often result in poor implementation due to increasing the workloads of others. 21 While hospitals are experiencing a shortage in nursing staff, PTs and OTs are available to work with patients; thus hospitals should reconsider work assignments related to patient mobilization.…”
Section: Introductionmentioning
confidence: 99%